France Kidrič danes - Hladnik, Miran (Jezik in slovstvo, 2001)
Although in contemporary literary history France Kidrič is a synonym for unpopular positivist biographism, he still holds primacy in his own generation; even more surprisingly, he remainds the most quoted author in recent Prešernian literature, thanks to the wealth of data he compiled. Citation statistics for the three central Slovene journals of literary history (Slavistična revija, Jezik in slovstvo, Primerjalna književnost) in the last five years show that the most quoted authors in the field in general are Janko Kos, Matjaž Kmecl, Franc Zadravec, Boris Paternu, and Dušan Pirjevec. In the literary history citation lists, older generations are increasingly giving way to younger ones.
Keywords: Kidrič, France, 1880-1950; Slovene literature; slovenska književnost; literarni zgodovinarji; literary historian; prešernoslovje; citiranje